2018
DOI: 10.1007/s00268-018-4820-6
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Between Plastic and Metallic Biliary Stent Placement in Patients Receiving Preoperative Neoadjuvant Chemoradiotherapy for Resectable Pancreatic Cancer

Abstract: Background The optimal stent type in patients receiving preoperative neoadjuvant chemoradiotherapy (NACRT) is uncertain. The present study aimed to compare the clinical effectiveness of biliary metallic stent (MS) and plastic stent (PS) in patients undergoing preoperative NACRT for resectable pancreatic cancer. Methods This retrospective study included 43 patients who required either biliary MS or PS before initiating NACRT for resectable or borderline resectable pancreatic head cancer. Seventeen patients had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 46 publications
1
53
0
Order By: Relevance
“…8,9,21 However, most of these studies are of retrospective design, and there is only one previous prospective randomized controlled trial. 8,9,[21][22][23] The previous prospective randomized controlled trial used three different regimens for NAC rather than a single regimen. 8 The present study is the first randomized controlled trial to compare the efficacy and safety of biliary drainage between FCSEMSs and PSs in BRPC patients with MBO undergoing the single NAC regimen (Nab-Paclitaxel/Gemcitabine).…”
Section: Discussionmentioning
confidence: 99%
“…8,9,21 However, most of these studies are of retrospective design, and there is only one previous prospective randomized controlled trial. 8,9,[21][22][23] The previous prospective randomized controlled trial used three different regimens for NAC rather than a single regimen. 8 The present study is the first randomized controlled trial to compare the efficacy and safety of biliary drainage between FCSEMSs and PSs in BRPC patients with MBO undergoing the single NAC regimen (Nab-Paclitaxel/Gemcitabine).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings show that the CMS was superior to the PS for biliary decompression during NAC-RT, with respect to RBO. 10,11 This study is the largest single-center comparison of stents used for biliary drainage in patients with pancreatic cancer undergoing NAC-RT. Furthermore, in this study, there was no difference in the surgical results, such as operation time, blood loss, and the R0 resection rate between the CMS and PS groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, a few studies recently confirmed that PS placement during preoperative chemotherapy was useful, but lacked sufficient volume for assessment. 10,11 In addition, neoadjuvant chemotherapy for locally advanced, unresectable tumors and conversion surgery have been reported as feasible options. We have been aggressively performing neoadjuvant chemotherapy for unresectable pancreatic tumors and have reported the usefulness of conversion surgery after chemotherapy.…”
mentioning
confidence: 99%
“…8 Many previous studies on biliary drainage for patients with unresectable pancreatic cancer indicated that a metal stent is superior to a plastic stent in terms of patency 9 ; however, a few recent studies also revealed longer patency and lower cost related to the stent occlusion of a metal stent than those of a plastic stent during NAC/NACRT. [10][11][12][13][14] It remains controversial which type of self-expandable metal stent (SEMS) is the most suitable for patients with resectable or borderline resectable pancreatic cancer during NAC/NACRT: an uncovered SEMS (USEMS), fully covered SEMS (FCSEMS) or partially covered SEMS (PCSEMS). During NAC/NACRT in patients with pancreatic cancer, the USEMS has been the standard SEMS for biliary decompression as well as during chemotherapy in patients with unresectable pancreatic cancer, but there have been few comparative studies on the patency and safety of SEMSs in curative surgery after neoadjuvant therapy.…”
Section: Open Accessmentioning
confidence: 99%